Child policy changes and estimation of income distribution effects - Eva MILITARU (Theoretical and Applied Economics, 2017)

(untitled)
The paper explores the household income distribution effects of recent changes in social benefit policy for families with children in Romania. The particular changes we examine are the amount growth of the main social benefit for children – the universal state allowance for children – and the increase of income threshold and benefit amount for the support allowance for families with children, an important means-tested social benefit. Our approach relies on ex-post impact evaluation of policy changes through income simulation using microdata at household level. We studied the effects within specific groups of families based on number of children, but we also estimated the effects on single-parent families. The results show that recent changes have contributed to the reduction of income inequalities in general by increasing the income level at the bottom and median of the income distribution. Larger families experience higher relative income growth, as the benefits are linked with family size and their pre-reform income levels are lower.